The development of medical networks through ICT in Japan - Tsutomu Nakamura (Netcom)
This paper examines how medical networks using Information and Communications Technology (ICT) have been constructed, and what kind of spatial impact they have on the existing medical care provision system. The results are reported below. In Japan, each prefecture implements its own regional health care program for the appropriate allocation of medical resources. However, regional disparities in such allocation have not yet been resolved. ICT applied to two cases (the Wakashio Medical Network in Chiba Prefecture and the Haniwa Health and Welfare Network in Miyazaki Prefecture) has promoted functional division and cooperation among medical institutions as well as the efficient use of resources on medical networks. Factors contributing to the construction of these networks and their continued utilization include strong leadership of central hospitals in the regions, and the fact that they have managed to solve problems related to system development and operation costs. However, differences in medical network awareness between doctors and patients, as well as the constraints of network maintenance costs, force participating doctors in ICT field. In this way, medical networks become a way to complement existing medical delivery systems.